Georeferencing and real-time temperature monitoring during the transport of human biological materials (Revista Contexto & Saúde, 2025)
Objective: To evaluate and compare the average temperature between active electric packaging and passive thermal packaging with artificial ice packs during the transport of human biological materials. Methods: The temperatures (in °C) of the transported biological samples were assessed over 6 consecutive days, using two different biological material transport boxes: (1) passive thermal box cooled with artificial ice packs, and (2) active electric box with a long-lasting lithium battery, cooled by a closed-circuit system using a compressor and coil. A total of 2,247.1 km was traveled, and 10,606 biological samples were collected across 11 different clinical analysis laboratories. Temperature monitoring was carried out through sensors installed in both boxes, allowing real-time online tracking and temperature monitoring. Results: On all analyzed days, the active box proved more efficient than the passive box, maintaining the average temperature within the established requirements (2 to 8°C) throughout the journey until final delivery. Environmental temperature variation did not directly affect the internal temperature of either packaging used in this type of transport. Conclusion: Active electric packaging is more efficient when compared to passive packaging cooled with artificial ice packs, as it maintained the correct temperature throughout the entire biological material transport process.